IL CLOWN – UNA METAFORA PER L’IDENTITÀ DELL’ARTISTA NEL CIRCO DELLA STORIA E DELL’ESISTENZA IN MATEI VIȘNIEC E NORMAN MANEA - DAVID, Emilia (Studia Universitatis Babeș-Bolyai Philologia, 2023)
The Clown – a Metaphor for the Artist Identity in the Circus of History and Existence at Matei Vișniec and Norman Manea. The paper will highlight affinities and differences in the way Norman Manea and Matei Vișniec, two prominent writers of the Romanian exile from the 80s, narrate the existential failure in the novel The Black Envelope and respectively in the play Old clown wanted, making extensive use of the modalities provided by an intensely poetic imaginary. The dreamlike representations, which acquire opposite connotations in the plots of the two authors, as well as certain image-metaphors, elaborated according to the models inspired by Federico Fellini, highlight some aspects that distinguish the perspective expressed by each writer regarding the dense and broad semantics of the circus. In Matei Vișniec’s play, the circus topos declines in the forms of precariousness, which defines the artist’s condition as well as the general human condition - perpetually threatened by the inexorable passage of Time. As for Norman Manea’s novel, the writer concentrates in this plot the perception of History as a buffoonish and vulgar manifestation, which condemns the individual, the artist in the first instance, to the status of victim. In this way, Manea and Vișniec actually explore the forms of manifestation peculiar to a cultural and linguistic imaginary related to the representation of individual and collective identity. Clovnul ‒ o metaforă pentru identitatea artistului în circul istoriei și al existenței la Matei Vișniec și Norman Manea. Articolul va evidenția afinităţi și diferenţe în modul în care Norman Manea și Matei Vișniec, doi scriitori marcanți ai exilului românesc din anii ’80, povestesc eșecul existențial în romanul Plicul negru și respectiv în piesa Angajare de clovn, recurgând amplu la instrumentele unui imaginar de natură intens poetică. Reprezentările onirice, care capătă conotații opuse în tramele celor doi autori, precum și anumite imagini-metafore elaborate după modele oferite de Federico Fellini, evidențiază aspecte care disting perspectiva exprimatǎ de fiecare scriitor referitoare la semantica densǎ şi amplǎ a circului. Ȋn piesa lui Matei Vișniec, toposul circului se declinǎ ȋn formele precaritǎții, care defineşte condiţia artistului precum şi pe cea general umană – ameninţată perpetuu de trecerea inexorabilă a Timpului. Cât priveşte romanul lui Norman Manea, scriitorul concentreazǎ ȋn aceastǎ tramǎ percepția Istoriei ca manifestare bufonescă şi vulgară, care condamnǎ individul, artistul în primă instanţă, la statutul de victimă. În acest mod, Manea și Vișniec explorează, de fapt, formele de manifestare proprii unui imaginar cultural și lingvistic legat de reprezentarea identității individuale și colective. Cuvinte-cheie: clovn, circ, artist, dictator, istorie, teatru în teatru, poeticitate Article history: Received 28 December 2022; Revised 28 January 2023; Accepted 12 February 2023; Available online 27 March 2023; Available print 31 March 2023.